An Evaluation of Supply Chain Management and Total Quality Management (TQM) Practices in Bangladesh Ready-made Garments Industry: A Conceptual Model - Farhana Rashid; Che Azlan Bin Taib; Mohd Akhir Hj. Ahmad (International Journal of Supply Chain Management, 2016)
Supply Chain Management (SCM) and Total Quality Management (TQM) are interrelated quality practices toward achieving better quality performance. For Bangladesh Ready-Made Garments had grown significantly over the last decades in every term but unfortunately quality of locally produced goods is still an issue. Total quality management (TQM) is increasingly being adopted by garments companies as an initiative to solve quality problems and to meet the needs of the final customer. However, TQM should incorporate the integrated quality management activities of members in the supply chain. This supply chain context is especially salient in the quality assurance of Bangladesh RMG sector. Therefore, this paper aims to delineate the supply chain management issues in TQM practices to gain the sustainability in Bangladesh RMG sector where HRM (Human Resource Management) play the mediating role. As, it is notable to mention that in case of Bangladesh RMG sector most of the existing literature give more emphasis and discuss about the infrastructural and strategic matters whereas TQM,SCM(Supply Chain Management) and HRM practices in an attempt to improve sustainable competitive advantage is still a debate both theoretically as well as empirically. In order to bridge this gap and to generate a more comprehensive argument, this paper further proposes and aims at providing a tool, a procedural framework, to ensure organizational sustainable competitive advantage. The proposed conceptual framework for the RMG industry provides a novel approach for decision makers of TQM practices and supply chain components to review and appraise the performance toward fulfillment of ultimate goals, i.e. producing high-quality garments product, and reducing the wastage of human labor, time and money. Proposed research direction and conclusion are discussed in conclusion of this paper. Keywords: Supply Chain Management, Total Quality Management, Sustainable Competitive Advantage, Human Resource Management practices, Ready-made Garments (RMG).